New end take off: regulating cell polarity during the fission yeast cell cycle - Martin, Sophie G; Chang, Fred (Cell cycle (Georgetown, Tex.), 2005)
Cell polarization is a major event of the cell cycle and underlies the function of most cells. Cell polarity is often achieved through the coordinated organization of the microtubule and act in cytoskeletons. Dramatic changes in cell polarization occur during the cell cycle and are subject to regulation by cell cycle controls. Cells of the fission yeast Schizosaccharomyces pombe grow by tip extension in a cell cycle-controlled manner. During G2 phase, these cells exhibit a transition in cell polarization known as New End Take Off (NETO), in which monopolar cells initiate bipolar growth. Dynamic microtubules contribute to this process by depositing at cell ends the microtubule plus end proteins tea1p and tea4p, which are necessary for NETO. We discuss here how these proteins may recruit for 3p, a formin responsible for actin nucleation, as well as two other actin binding proteins, bud6p and sla2p, to initiate cell polarization at the new end of the cell. Thus, the study of NETO is revealing a mechanism by which the plus ends of microtubules regulate the spatial organization of actin.